Professional and pedagogical competencies in learning factual paragraph reading aspects - Lili Siti Nurwahidah; Deasy Aditya Damayanti; Roro Tri Nur Herthira; Eva Julianti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to explore: 1) the professional competence of elementary school high-graduate teachers in learning factual paragraph reading skills; 2) the pedagogical competence of elementary school high-graduate teachers in learning factual paragraph reading skills. The population of this study consisted of 32 elementary school high-grade teachers in Malangbong District, who submitted questionnaires via Google Forms. The sample consisted of up to 30 teachers, determined using statistical formulas. Data on the professional and pedagogical competence of elementary and high school teachers in learning factual paragraph reading skills were collected using a Google Form-based questionnaire compiled through objective and systematic procedures to ensure it met the requirements of a valid instrument. Data on the professional and pedagogical competence of elementary school high-grade teachers in learning factual paragraph reading skills were analysed using parametric inferential statistical procedures, specifically the one-sample t-test. The results of the study: 1) the professional competence of elementary school and high school teachers in learning factual paragraph reading skills is in the high category; 2) the professional competence of elementary school and high school teachers in learning factual paragraph reading skills is in the high category too